81: Is Epidural Analgesia in Labor Associated with Respiratory Distress in Late Preterm Infants? – a Retrospective Cohort Study. Issue 6 (1st June 2014) - Kumar, M; Rylance, H; Ijaz, Z; Senthilselvan, A
Abstract: BACKGROUND: Epidural analgesia is the commonest mode of providing analgesia during labor, with a combination of bupivacaine and fentanyl most often used in practice. Pharmacokinetic studies have shown that opioids diffuse freely from the epidural space into maternal blood and across the placenta. OBJECTIVES: To test whether late-preterm infants exposed to opioids from maternal epidural analgesia in labor are more likely to develop respiratory distress in the immediate neonatal period. DESIGN/METHODS: Singleton babies of 33 to 36 weeks gestation, born between the dates of January 1, 2006 to December 31, 2011 at two hospital sites in Edmonton were eligible for recruitment. Subjects with major congenital malformations, culture proven sepsis, or birth by elective caesarean section without onset of labor were excluded. The outcomes of babies exposed to epidural analgesia (Exposed group) were compared with babies without epidural exposure (Unexposed group) adjusting for the following variables, ie, gestational age at birth, infant's sex, site of birth, antenatal steroids, maternal diabetes and hypertension, oligohydramnios, route of delivery and other modes of analgesia used in labor. The outcomes of interest were Apgar scores at 1 min and 5 min, need for resuscitation (defined as need for any one of the following in the delivery room – bag and mask ventilation, intubation, chest compression or resuscitation drugs) and development of respiratory distress within 24 h of birth. RESULTS: We recruited 1045 infants; 12.5% needed resuscitation in the delivery room and 15.6% developed respiratory distress following admission to the NICU. 58.6% subjects were exposed to epidural analgesia in labor. The exposure to epidural analgesia was associated with lower 1 min (P=0.009) and 5 min (P<0.001) Apgar scores but not with greater need for resuscitation (P=0.43) or the development of respiratory distress (OR 1.30 [95% CI 0.86 to 1.96]; P=0.220). In subgroup analysis, we noted a trend towards higher incidence of respiratory distress in infants at 33 to 34 weeks gestation (OR 1.45 [95% CI 0.91 to 2.30]; P=0.11) exposed to epidural analgesia. CONCLUSIONS: Exposure to maternal epidural analgesia was associated with lower Apgar scores in late preterm infants with a trend towards higher risk of development of respiratory distress in more immature infants.